About signals allowing to provide sustainability to impacts of short-term and or focused on spectrum interference - G. Zhilyakov, Evgeny; P. Belov, Sergey; V. Ursol, Denis (International Journal of Engineering and Technology, 2018)
The growth of telecommunication technology application intensity generates the problem of mutual influence concerning the systems which generate them. This influence distorts the signals providing information interaction, which allows us to talk about the mutual interference created by them.It is proposed to use basic functions in the work in the work to combat short-term interference in comparison with signal duration. One of the function fragments can be calculated from the others. In its turn, one should use basic functions in order to combat narrow-band interference, some fragments of the Fourier spectra of which can be calculated from the others.It was shown that it is useful to use the eigenfunctions of symmetric operators determined non-negatively as the transmitted signals. Relations are obtained that express certain fragments of signals through others.In order to combat narrow-band interference, it is proposed to use the intrinsic functions of subband nuclei as basic functions. They obtained the relations, which allow us to recover the distorted fragments of their spectra.Thus, they developed the theoretical basis to counter short-term and narrow-band interference during the transmission of information.